2018
DOI: 10.1016/j.jpedsurg.2018.02.091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an artificial placenta on brain development and injury in premature lambs

Abstract: Research study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The AP did not encumber regional cerebral oxygenation, blood flow, and autoregulation in 2‐day long experiments 102 . Normal cerebral maturation and absence of white matter injury (WMI) and intracranial hemorrhage (ICH) was found in animals supported for 1 week 107 . Examination of the gastro‐intestinal tract showed mild small bowel epithelial injury despite preserved mucosal architecture.…”
Section: Current Successful Ap and Aw Models: Design And Outcomesmentioning
confidence: 91%
“…The AP did not encumber regional cerebral oxygenation, blood flow, and autoregulation in 2‐day long experiments 102 . Normal cerebral maturation and absence of white matter injury (WMI) and intracranial hemorrhage (ICH) was found in animals supported for 1 week 107 . Examination of the gastro‐intestinal tract showed mild small bowel epithelial injury despite preserved mucosal architecture.…”
Section: Current Successful Ap and Aw Models: Design And Outcomesmentioning
confidence: 91%
“…[7][8][9][10] Other investigators have reported the successful application of artificial-placenta based therapies for up to h with similar concepts and extracorporeal gas exchange systems. [11][12][13][14] Accordingly, the feasibility of long survival with a pumpless extracorporeal system has been well documented in the experimental literature.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The concept of an artificial placenta (AP), whereby gas exchange is achieved using an extracorporeal membrane oxygenator (ECMO) connected to the fetal circulation via the umbilical vessels has been investigated since the 1950s (Westin et al, 1958). Recent research has established the feasibility of AP support of preterm sheep for periods of up to a month using a pumpless ECMO circuit (Arens et al, 2011; Church, Coughlin, et al, 2018; Church, Perkins, et al, 2018; Church, Werner, et al, 2018; El‐Sabbagh et al, 2018; Gray et al, 2013; Hornick et al, 2018; Lawrence et al, 2018; Miura et al, 2012, 2015, 2016; Partridge, Davey, Hornick, McGovern, et al, 2017; Reoma et al, 2009; Rochow et al, 2013; Schoberer et al, 2014; Usuda et al, 2017, 2019; Westin et al, 1958; Zapol et al, 1969). Importantly, two groups have provided evidence of near‐normal fetal growth and development using this approach without any of the typical organ injury associated with preterm birth (Hornick et al, 2018; Partridge, Davey, Hornick, McGovern, et al, 2017; Usuda et al, 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%